Moyamoya disease in pregnancy: maintenance of maternal blood pressure - Barrett, Helen L (Obstet Med, 2011)
Moyamoya disease is a rare cerebrovascular occlusive disorder characterized by stenosis in the circle of Willis with the development of a compensatory circulation. It has been associated with significant morbidity in pregnancy including intracranial haemorrhage, ischaemic stroke and epilepsy. We present the case of a 26-year-old woman with a previous diagnosis of moyamoya vasculopathy with bilateral superficial temporal to middle cerebral artery bypass grafting. During the second trimester, she developed significant neurological symptoms related to postural hypotension in the presence of a stenosis of the right-sided graft. The hypotension was treated with fludrocortisone therapy with improvement in blood pressure and symptoms. Moyamoya vasculopathy poses unique challenges to obstetric care. This is the first report of use of fludrocortisone for maintenance of blood pressure during pregnancy in this condition.